Sulfate resistance testing of shotcrete – Sample preparation in the field and under laboratory conditions. (22nd March 2021) - Kaufmann, Josef; Loser, Roman; Winnefeld, Frank; Leemann, Andreas
Highlights: Sulfate resistance testing of shotcrete. New method for test sample preparation in the laboratory without spraying. Comparison of laboratory-prepared with real on-site shotcrete. Chemical phase assemblage of shotcrete before and after sulfate interaction. Effect of alkali-free accelerators and different cement types on the sulfate resistance of shotcrete. Abstract: When shotcrete is in contact with sulfate containing ground water, there is a risk of a drastically reduced service life. In this case, the use of sulfate-resisting cement is recommended. Since physical characteristics of the cement matrix of shotcrete differ from conventional concrete, sulfate-resisting cements do not always guarantee sufficient shotcrete durability. Thus, testing of the sulfate resistance in accelerated tests is necessary. Providing test samples from on-site (real) shotcrete is time consuming and demanding. In this study, the sulfate resistance and physical properties such as compressive strength and transport properties of samples produced in the laboratory without spraying are compared to the properties of field samples. A new compaction method is proposed, which is apt to allow high accelerator dosages. For different alkali-free set-accelerators and cement types, the laboratory-produced samples not only reveal similar sulfate resistance test results as on-site shotcrete, but also exhibit comparable porosity, transport properties and chemical phase assemblage.